2011
DOI: 10.1002/ajhb.21227
|View full text |Cite
|
Sign up to set email alerts
|

Birth weight, postnatal weight gain, and adult body composition in five low and middle income countries

Abstract: Objectives-Evaluate associations between birth weight (BW), infancy and childhood weight gain and adult body composition.Methods-Subjects included participants of five birth cohort studies from low and middle income nations (Brazil, Guatemala, India, Philippines, South Africa; n=3432). We modeled adult body composition as a function of BW and conditional weight gain (CW), representing changes in weight trajectory relative to peers, in three age intervals (0-12m, 12-24m, 24m-mid childhood).Results-In 34 of 36 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
92
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(109 citation statements)
references
References 47 publications
12
92
0
3
Order By: Relevance
“…This influence is aligned with previous studies 22 . Similarly, the differences in the hip and abdominal skinfold thicknesses, as well as in the indices of central fat distribution (waist-hip and skinfold ratios) seen in the LBW and HBW are in accordance with earlier findings 17,23 . It seems that both low and excessive birth weight can predict more strongly adult adiposity than adult lean mass.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This influence is aligned with previous studies 22 . Similarly, the differences in the hip and abdominal skinfold thicknesses, as well as in the indices of central fat distribution (waist-hip and skinfold ratios) seen in the LBW and HBW are in accordance with earlier findings 17,23 . It seems that both low and excessive birth weight can predict more strongly adult adiposity than adult lean mass.…”
Section: Discussionsupporting
confidence: 79%
“…In human, these observations were replicated in both from industrialized countries 7 and also those undergoing the nutritional transition 17,18 . In African countries, previous studies have shown the effects of birth weight on growth and development during childhood 19 .…”
Section: Discussionsupporting
confidence: 58%
“…Poor intrauterine growth affecting weight at birth has been linked to adverse outcomes later in life [15][16][17][18][19][20] . This 'developmental programming' hypothesis propounded by David Barker and colleagues posits that a stimulus or insult during a critical period of foetal growth and development that causes perturbations of the maternal-placental-foetal unit can cause permanent changes in metabolism, structure and function of foetal organs and systems 15,21 .…”
Section: Early Life Growth and Developmentmentioning
confidence: 99%
“…Studies on early origins of diseases have identified early life determinants of excess body fat accumulation [4,5]. The first years of life are critical periods of development.…”
Section: Introductionmentioning
confidence: 99%